Repurposing MOOC learning for academic credit: A survey of practice in University Work Based Learning departments in England and Wales. (15th November 2017) - Talbot, Jon
This small study is an investigation into the potential for converting learning from MOOCs into credit bearing qualifications in universities. The mechanism for achieving such conversion is the use of what is variously known as the Accreditation or Recognition of Prior Learning (A/RPL). The evidence suggests such practices in the UK are heavily concentrated in Work Based Learning (WBL) departments. This study investigated practices in 26 WBL departments in England and Wales. The results indicate there is very little awareness of the potential of MOOC learning as the basis for A/RPL claims among tutors in WBL departments. Moreover there are relatively few departments which have sufficiently flexible procedures to integrate MOOC learning into curricula. At a time when policy makers are seeking the removal of barriers to the recognition of informal and non-formal learning, it seems there are few opportunities for those completing MOOC courses in England and Wales to convert them into recognised qualifications. The study provides evidence that in the UK completion of MOOC courses is unlikely to result in accredited qualifications.